IMPLEMENTASI PROGRAM INFORMASI PENJUALAN SPAREPART SEPEDA MOTOR BERBASIS E-CRM DI TOKO HENDRIK SPAREPART RAWANG PANCA ARGA - Maryana, Siti; Agus, Raja Tama Andri; Mardalius, Mardalius (STKIP PGRI Tulungagung, 2025)
Hendrik Spare Parts Shop in Rawang Panca Arga, Asahan Regency, is a motor vehicle shop that has been operating for a long time and has a good reputation in its area. However, as the business develops and operations become increasingly complex, this store faces challenges in maintaining good relationships with customers and optimizing the sales process. Currently, their customer recording process is still done manually, which is time consuming and prone to errors. In developing e-CRM for the Hendrik Sparepart Store, a series of features will be designed that aim to improve customer experience, strengthen customer relationships and increase customer loyalty. One of the main features that will be included in this e-CRM application is a discount or promotion program that can be adjusted to customer offers. Hendrik Sparepart Shop sells various types of tires with a total of 60 units. Apart from tires, there are 40 units of engine oil for sale. Other products include 20 units of spark plugs, 15 units of air filters, 30 units of front brake pads, and 25 units of rear brake pads. By implementing an application-based information system for customer relationship management, Toko Hendrik Sparepart is expected to increase customer satisfaction and strengthen customer relationships. , and increase customer loyalty. Apart from that, it is hoped that this application will also provide more accurate and real-time information about customer needs, to facilitate more informed decision making in improving the customer experience